Physical Management of Patient with Osteoarthritis of Knee - Khan, Md Moniruzzaman; Salek, AKM; Ahmed, Syed Mozaffar; Ferdous, Jannatul; Moyeenuzzaman, Md (Bangabandhu Sheikh Mujib Medical University Journal, 2010)
Osteoarthritis (OA), is by far the most common form of arthritis. It shows a strong association with ageing and is a major cause of pain and disability in the elderly. Pathologically, it may be defined as a condition of synovial joints characterized by focal loss of articular hyaline cartilage with proliferation of new bone and remodelling of joint contour. Inflammation is not a prominent feature, OA preferentially targets the weight bearing joint mainly knee & hip. There is no single cause of OA; it results from a disparity between the stress applied to the articular cartilage and the ability of the cartilage to withstand that stress. The initial or early OA treatment aimed at relieve of pain, restoration of joint movement and rest of the joint with the support of analgesic and NSAIDS. Shortwave diathermy (SWD) and ultrasound therapy is also helpful in relieving pain and joint stiffness. For long term management full explanation of the nature of OA and advice and instruction on appropriate exercise program is essential. Reduction of any adverse mechanical factors - these includes weight loss if obese, shock -absorbing footwear, use of walking stick or walker. DOI: 10.3329/bsmmuj.v2i2.4770 BSMMU J 2009; 2(2): 95-98